A STUDY OF FOOTPRINTS OF TREE-CLIMBING COMMUNITIES OF SOUTH INDIA - Bhat, P. Shivarama; Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2014)
The paper details the morphological adaptations of the foot shape and its arches to sustained professional tree climbing activity. Foot inversion, as required by climbers on a long term and regular basis reshapes the bony architecture of the foot and the medial longitudinal arch over a period of time. These changes can be observed and measured, noninvasively through study of footprints.This community study on the progressive adaptation of the arch to the rigors of climbing was recorded through footprints collected from the climbers with varied experience in the profession. The collation of observations show that the medial arch continues to shrink with sustained inversion, raising the dome of the instep.The progressive compensatory rise in arch height however, is arrested abruptly after a phase, with failure of the arch to accommodate further to more stress – leading to slipping and falls from heights. The article discusses the bio-mechanisms and kinetics of foot adaptation to the rigors of climbers and analysis the cause of accidental falls, even though most of the accidental fall victims have had a number of years of climbing experience.
Keywords: medial longitudinal arch; foot; coconut palm; community; inversion